Interventions to Relieve the Burden on Informal Caregivers of Older People with Dementia: A Scoping Review - Celia Encinas-Monge; Sergio Hidalgo-Fuentes; Elena Cejalvo; Manuel Martí-Vilar (MDPI AG, 2024)
Dementia increases dependence in older adults and decreases their quality of life and that of their family members. These family members often take on the responsibility of caregiving and suffer from burden and health deterioration due to facing various stressors. The aim is to verify the effectiveness of existing interventions aimed at relieving the burden and stress of informal caregivers of older people with dementia. A scoping review was conducted by consulting the Web of Science, Scopus, ProQuest, and PubMed databases, following the guidelines of the PRISMA 2020 Statement. The review protocol has been registered in PROSPERO under number CRD42024558609. Twenty-six articles met the inclusion criteria and were reviewed, studying the type of intervention design, the sample size of caregivers and their main characteristics, the duration and follow-up, and the variables investigated with their respective measurement instruments. The analysis of the different studies showed that the most developed types of interventions are psychoeducational and cognitive-behavioral therapies, both individual and group. These interventions were mainly effective in reducing the burden and depressive symptoms of caregivers. It is considered advisable to implement more randomized controlled trials for further research, because as the number of caregivers increases, so does the need for affordable and effective interventions.